Biologic and molecular markers for staging colon carcinoma. (February 2016) - Bejarano, Pablo A; Garcia-Buitrago, Monica T; Berho, Mariana; Allende, Daniela
Biomarkers in the field of pathology and oncology may allow for the detection of disease, assessment of prognosis or to predict response to certain therapy. Molecular abnormalities in colorectal cancer genesis may occur due to chromosome instability, microsatellite instability and DNA methylation (CpG island methylator phenotype). These alterations are associated in some cases to sporadic carcinomas whereas in others are seen in syndrome-related tumors and are the basis for the use of different biomarkers in the clinical setting. These may include mismatched repair gene/proteins, RAS, BRAF, PIK3CA, which help to determine tumor prognosis and predict response to certain drugs.